Macro-invertebrates response to acute salinity changes in the Shatt Al-Arab River system, Southern Iraq - Mohammed, Hanaa H.; Ahmed, Huda K.; Al-Taei, Samer A.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2023)
The stress of acute salinity increase on the life of macro-invertebrates in Shatt Al-Arab River system were investigated based on their abundance estimation acute salinity increase during the year 2018,where the salinity of the River at central, Basrah City became above 5 ppt and reached up to 25 ppt. Review work was done to determine the sizes and densities of the species during the normal conditions in past decades (1975-1995). The results of observations, photography and semi-quantitative sampling which were taken during many visits in the years 2012, 2015, 2016, 2016, 2017, 2018, 2019 and 2020 at Al-Salhia, Abo Al-Kassib, Al-Garmma and Al-Gurnah, were expressed in an ordinal six abundant scales (SACFOR), modified for species sizes and densities. All the species were have superabundance or common scale during the period 1975-1995, whereas at 2018-2020 the abundance of all species except M. affinis, were declined in general, 7 species were absent and 3 more were rare. The amphipods Parhyale basrensis, Platorchestia monodi, the isopod Sphaeroma annandalei and the annelid Namalycastis indica were commonly or frequently found at good state indicating their ability to resist the mesohaline conditions, the euryhaline species M. affinis and B. amphitrite weren’t affected. The study concluded that, in case of long term mesohaline conditions, most of the estuarine macro-invertebrates will be unable to persist and may be shifting to the upper reaches of the River.